(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
This article examines the sociolinguistic transformation of advertising in Morocco. It mainly focuses on the integration of Moroccan Arabic (Darija) in influencer marketing. Historically, Moroccan advertising has relied on French and Modern Standard Arabic (MSA). This usage reflects class hierarchies and formal authority. However, the rise of digital platforms and social media influencers has brought a shift toward new, informal, localized, and affective modes of communication. Based on the literature in media studies, sociolinguistics, and marketing, this review shows how Darija has become a strategic linguistic resource to create cultural intimacy and audience engagement. The article tries to cover data from traditional advertising to influencer culture in order to examine language ideologies and hierarchies in Morocco. The goal is to see the commodification of Darija within globalized marketing practices. By reviewing different studies and theoretical frameworks, this paper argues that the popularity of Darija in digital content is not simply a marketing trend, but a reflection of particular sociocultural changes. Therefore, this paper offers a critique on how language, identity, and consumer behavior are linked together in the context of Moroccan digital advertising.